THE IMPACT OF AVAILABILITY OF MANAGERIAL SKILLS ON THE EFFICIENCY OF ENGINEERS IN SAUDI ARABIA - Robert J. Hanson (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In the contemporary world, managers play various roles in line with the management. Consequently, they require different skills to meet the challenges that come along with their function. A significant number of studies have been carried in the past in a bid to elucidate the relationship between management skills and the efficiency with regard to various projects or organization. This is as a result of the fact that the global market has developed needs for organizations to embrace effectiveness and efficiency especially in the management of critical projects. This research paper seeks to examine the impact of the availability of managerial skills on the effectiveness of engineers who are working in the electricity companies.This cross- sectional descriptive study was carried out among Saudiemployees from October to December 2015, a sample size of 43 employees were participated in this study. Proper questionnaire was designed to collect data from target group, data was analyzed by SPSS version 19.The main findings of this research, listening to the demands of professionals by engineers solve their problems and increase the work output and finally the availability of managerial skills have a significant effect on the efficiency of Engineers working at the electricity companies in Saudi Arabia.